2023
DOI: 10.1002/smll.202302842
|View full text |Cite
|
Sign up to set email alerts
|

Attack Resilient True Random Number Generators Using Ferroelectric‐Enhanced Stochasticity in 2D Transistor

Abstract: By harnessing the physically unclonable properties, true random number generators (TRNGs) offer significant promises to alleviate security concerns by generating random bitstreams that are cryptographically secured. However, fundamental challenges remain as conventional hardware often requires complex circuitry design, showing a predictable pattern that is susceptible to machine learning attacks. Here, a low‐power self‐corrected TRNG is presented by exploiting the stochastic ferroelectric switching and charge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Furthermore, Chien et al . demonstrated the utilization of cycle-to-cycle variation in MoS 2 memtransistors for computing security applications [ 115 ]. This suggests that while device variation presents challenges, it can also be leveraged to enable novel functionalities and applications.…”
Section: D Material-based Device Performance Metricsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, Chien et al . demonstrated the utilization of cycle-to-cycle variation in MoS 2 memtransistors for computing security applications [ 115 ]. This suggests that while device variation presents challenges, it can also be leveraged to enable novel functionalities and applications.…”
Section: D Material-based Device Performance Metricsmentioning
confidence: 99%
“…For instance, Sebastian et al [102] and Zheng et al [110] utilized the device-to-device variation in MoS 2 -based memtransistors to develop a random number generator and construct a Bayesian network for applications where uncertainty plays a crucial role. Furthermore, Chien et al demonstrated the utilization of cycle-to-cycle variation in MoS 2 memtransistors for computing security applications [115]. This suggests that while device variation presents challenges, it can also be leveraged to enable novel functionalities and applications.…”
Section: Device-to-device Variation and Cycle-to-cycle Variationmentioning
confidence: 99%
See 1 more Smart Citation